Matilda Peppercorn - Manx - Marshall, Jill (Pear Jam Books, 2011)
Matilda Peppercorn is being watched. Weirdy women keep popping up in all sorts of unexpected places, in her garden; at her kickboxing contest; up a tree at the creepy Ruins when she's with her best friend Mattan Lundquist. What's more, they're not just watching they're testing. But what for?